Towards a Feminist Public Theology: on Wounds, Scars and Healing in the Book of Jeremiah and Beyond - Claassens, L. Juliana M. (International journal of public theology, 2019)
In this article, I am contributing to the ongoing conversation on a feminist public theology. Drawing on examples of feminist public theologians in my own context in (South) Africa, I propose that a feminist public theology ought to deal honestly and constructively with the reality of the deep wounds and the scars caused by racism, sexism, xenophobia, and homophobia, which, if left unattended, may fester and return with a vengeance. It is also imperative that a feminist public theology continues to imagine the world to be otherwise, thus helping not only to name the injustice of the past, but also to be able to see beyond the violence to help foster values such as compassion, justice, resistance and resilience. Drawing on examples from the book of Jeremiah, I will illustrate something of my own vocation as a feminist public theologian in the context of South Africa today.